A review of math-based CAE tools for rollover simulations. (20th April 2009) - Chou, Clifford C.; Wagner, Christina D.; Yang, King H.; King, Albert I.; Hu, Jingwen; Hope, Karrie; Arepally, Sudhakar
This article presents a review of math-based models simulating rollover events under various test conditions. The types of model reviewed include rigid-body- and deformable-body-(or finite-element-) based models. Rigid-body-based models consist of those developed using packages including ADAMS, HVE, CarSim, Truck-Sim, MADYMO, CAL3D and PC-Crash. Deformable-body-based models require the use of non-linear crash analysis codes, such as LS-DYNA, Pam-Crash or RADIOSS. Simulations of the SAE J2114 rollover test procedure using both types of model are demonstrated. Model limitations and issues are addressed in regards to model applicability to potential users/modellers. Potential areas of further improvements over these models are also presented.